2005
DOI: 10.1128/jvi.79.17.11467-11475.2005
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus IE1-72 Activates Ataxia Telangiectasia Mutated Kinase and a p53/p21-Mediated Growth Arrest Response

Abstract: Human cytomegalovirus (HCMV) encodes several proteins that can modulate components of the cell cycle machinery. The UL123 gene product, IE1-72, binds the Rb-related, p107 protein and relieves its repression of E2F-responsive promoters; however, it is unable to induce quiescent cells to enter S phase in wild-type (p53 ؉/؉ ) cells. IE1-72 also induces p53 accumulation through an unknown mechanism. We present here evidence suggesting that IE1-72 may activate the p53 pathway by increasing the levels of p19Arf and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 83 publications
(96 reference statements)
1
76
0
Order By: Relevance
“…Furthermore, many reports have described a viral connection between TP53 and cell cycle arrest. Herpesviruses, such as herpes simplex virus (40), human herpesvirus 6 (41), and human cytomegalovirus (42)(43)(44), cause cell cycle arrest via the TP53 pathway; however, the viral proteins responsible for TP53 stabilization and the precise mechanisms and significance of cell cycle arrest remain unknown. The data in this study might provide a clue to the mechanism and the significance of cell cycle arrest induced by these viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many reports have described a viral connection between TP53 and cell cycle arrest. Herpesviruses, such as herpes simplex virus (40), human herpesvirus 6 (41), and human cytomegalovirus (42)(43)(44), cause cell cycle arrest via the TP53 pathway; however, the viral proteins responsible for TP53 stabilization and the precise mechanisms and significance of cell cycle arrest remain unknown. The data in this study might provide a clue to the mechanism and the significance of cell cycle arrest induced by these viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Several herpesviruses, such as HSV (Boutell & Everett, 2004), EBV (Mauser et al, 2002), HCMV (Castillo et al, 2005) and HHV-6B (Øster et al, 2005), have been shown to induce phosphorylations at multiple sites in p53. Only two viruses, EBV and human T-cell lymphotropic virus type 1, have previously been reported to induce phosphorylation of human p53 at Ser392 (Pise-Masison et al, 1998;Mauser et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Human cytomegalovirus (HCMV) (Speir et al, 1994;Muralidhar et al, 1996;Tsai et al, 1996;Bonin & McDougall, 1997;Castillo et al, 2005) and possibly HHV-6A (Kashanchi et al, 1997;Takemoto et al, 2005) and HHV-6B (De Bolle et al, 2004;Takemoto et al, 2004;Øster et al, 2005) interfere with the tumour suppressor protein p53. The major functions of p53 are associated with maintaining the integrity of the genome by inducing cell-cycle arrest, senescence or apoptosis (Jin & Levine, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Human cytomegalovirus stimulates p53 activity, leading to a p21-dependent inhibition of cell cycle progression. 48 The EBVencoded protein ZTA was found to cause a G 1 -arrest by inducing p53 and the cdk inhibitors p21 and p27 as well as accumulation of hypophosphorylated (growth-suppressive) Rb. 45,49 Replication of MHV prevents cdk4/6 activity and subsequent Rb hyperphosphorylation by a reduction of G 1 cyclins (cyclin D1, D2, D3 and cyclin E).…”
Section: Viral Interference With the Cell Cycle Programmentioning
confidence: 99%